Decision support tools for climate change mitigation interventions in agriculture - Costa, Ciniro (Bioversity International and the International Center for Tropical Agriculture, 2022)
A presentation by Ciniro Costa Junior on the Decision Support Tools (DST) for climate change mitigation interventions in Agriculture. A presentation series under the AGNES Climate Governance, Diplomacy and Negotiations Leadership Program. Presented on Monday, August 22, 2022.